PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP MANAJEMEN LABA PADA SEKTOR INDUSTRI BARANG KONSUMSI - Angeliza Prasetio; yulius Jogi Christiawan (Business Accounting Review, 2016)
This research’s purpose was to know whether there was a relationship between corporate social responsibility with earning management. Corporate social responsibility was measured with CSR index that was valued with guideline criterias from GRI 3.1. In this research, earning management measured by discretionary accruals with modified Jones model. The control variables used in this research were leverage, firm size, and market to book ratio. This research examines a consumption good company that registered in Indonesia Stock Exchange in 2010-2014. This research found that CSR had no influence towards earning management.